Prenatal diagnosis of Wolf-Hirschhorn syndrome (4p-) in association with congenital hypospadias and foot deformity - Ermis Hayri; Basaran Seher; Karaca Nilay; Aslan Halil; Ceylan Yavuz (BMC, 2003)
Abstract Background Wolf-Hirschhorn syndrome is caused by distal deletion of the short arm of chromosome 4 (4p-). We report a case in which intrauterine growth restriction, hypospadias and foot deformity were detected by prenatal ultrasound examination at 29 weeks of gestation. Case Presentation A 31-year-old gravida 2 partus 1 woman was referred at 29 weeks' gestation with suspicion of intrauterine growth restriction. Sonographic examination revealed deformity of the right lower limb and undescended testes with an irregular distal penis. A cordocentesis was performed and chromosome analysis revealed a 46,XY,del(4)(p14) karyotype. Conclusion The prenatal detection of intrauterine growth restriction, hypospadias and foot deformity should lead doctors to suspect the presence of Wolf-Hirschhorn syndrome.